2016
DOI: 10.1148/radiol.2016151149
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Low versus High Recurrence Scores in Estrogen Receptor–Positive, Lymph Node–Negative Invasive Breast Cancer on the Basis of Radiologic-Pathologic Features: Comparison with Oncotype DX Test Recurrence Scores

Abstract: Purpose To review mammographic, ultrasonographic (US), and magnetic resonance (MR) imaging features and pathologic characteristics of estrogen receptor (ER)-positive, lymph node-negative invasive breast cancer and to determine the relationship of these characteristics to Oncotype DX (Genomic Health, Redwood City, Calif) test recurrence scores (ODRS) for breast cancer recurrence. Materials and Methods This institutional review board-approved retrospective study was performed in a single large academic medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
35
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 20 publications
6
35
2
Order By: Relevance
“…None of the morphologic features we examined in our series, including tumor grade, biopsy site changes, cellular stroma, or inflammatory cells, were associated with RS ≥ 18. We found that higher RS was associated with lower PR expression by IHC and lower PR mRNA scores ( P ≤ 0.007), in agreement with the literature [32, 33, 3638]. This finding suggests that low PR expression by IHC may be used to guide the use of the 21-gene RS assay for the favorable subtypes of breast carcinoma, but larger series are needed.…”
Section: Discussionsupporting
confidence: 90%
“…None of the morphologic features we examined in our series, including tumor grade, biopsy site changes, cellular stroma, or inflammatory cells, were associated with RS ≥ 18. We found that higher RS was associated with lower PR expression by IHC and lower PR mRNA scores ( P ≤ 0.007), in agreement with the literature [32, 33, 3638]. This finding suggests that low PR expression by IHC may be used to guide the use of the 21-gene RS assay for the favorable subtypes of breast carcinoma, but larger series are needed.…”
Section: Discussionsupporting
confidence: 90%
“…However, as reported, there was a markedly low interobserver agreement and a wide variability in predicting the RS, based on the imaging characteristics alone (regardless of years of experience as breast imagers), suggesting that imaging findings alone cannot consistently predict the risk of recurrence or whether chemotherapy is needed. More recently, Dialani et al reported that oval shape on mammograms, the presence of vascularity and posterior acoustics on ultrasound images, and lobulated shape on MR images, in combination with low ER positivity, PR negativity, and HER2 positivity, were associated with high recurrence scores.…”
Section: Discussionmentioning
confidence: 99%
“…Correlating genomic information with image findings is a new field of research, and the overlap between imaging features and genomic characteristics in breast cancer is not well established. The ability to estimate the likelihood of recurrence on the basis of molecular profile and imaging findings could become an important noninvasive tool for stratifying patients according to prognosis, allowing clinicians to make personalized tailored treatment decisions for an individual patient . Our goal was to measure lesion ADC value at 3T and to assess correlation with ODxRS scores.…”
mentioning
confidence: 99%
“…Most patients with hormone receptor (HR)‐positive, lymph node‐negative breast cancers have a favorable prognosis, and therefore, at least 85% of patients would be overtreated if adjuvant chemotherapy was offered to everyone . Recently, several multigene markers have been developed for predicting prognosis and effectiveness of treatment in breast cancer . These include the 70‐gene MammaPrint microarray assay, the 21‐gene Oncotype DX assay, and the 50‐gene PAM50 assay .…”
mentioning
confidence: 99%